2019
DOI: 10.1017/s2040174419000333
|View full text |Cite
|
Sign up to set email alerts
|

Maternal physical activity-induced adaptive transcriptional response in brain and placenta of mothers and rat offspring

Abstract: Maternal physical activity induces brain functional changes and neuroplasticity, leading to an improvement of cognitive functions, such as learning and memory in the offspring. This study investigated the effects of voluntary maternal physical activity on the gene expression of the neurotrophic factors (NTFs): BDNF, NTF4, NTRK2, IGF-1 and IGF-1r in the different areas of mother’s brain, placenta and foetus brain of rats. Female Wistar rats (n = 15) were individually housed in voluntary physical activity cages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Potential biological mechanisms such as placental transfer has been suggested ( Robinson and Bucci, 2012 ). An animal study on rats investigated the effects of maternal physical activity on gene expression of the neurotrophic factors, and upregulation was found in placenta of the very active mothers ( Fragoso et al, 2020 ). Additionally, other studies found voluntary exercise during pregnancy significantly increased the level of neurotrophic factors protein in hippocampus of rat pups; and female offspring born to pregnant mice with voluntary running wheels showed enhanced cell proliferation in the dorsal hippocampus ( Akhavan et al, 2013 ; Yau et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potential biological mechanisms such as placental transfer has been suggested ( Robinson and Bucci, 2012 ). An animal study on rats investigated the effects of maternal physical activity on gene expression of the neurotrophic factors, and upregulation was found in placenta of the very active mothers ( Fragoso et al, 2020 ). Additionally, other studies found voluntary exercise during pregnancy significantly increased the level of neurotrophic factors protein in hippocampus of rat pups; and female offspring born to pregnant mice with voluntary running wheels showed enhanced cell proliferation in the dorsal hippocampus ( Akhavan et al, 2013 ; Yau et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%